Clinical correlates of vitamin D deficiency in established psychosis. Issue 1 (December 2016) - Lally, J.; Gardner-Sood, P.; Firdosi, M.; Iyegbe, C.; Stubbs, B.; Greenwood, K.; Murray, R.; Smith, S.; Howes, O.; Gaughran, F.
Abstract Background Suboptimal vitamin D levels have been identified in populations with psychotic disorders. We sought to explore the relationship between vitamin D deficiency, clinical characteristics and cardiovascular disease risk factors among people with established psychosis. Methods Vitamin D levels were measured in 324 community dwelling individuals in England with established psychotic disorders, along with measures of mental health, cardiovascular risk and lifestyle choices. Vitamin D deficiency was defined as serum 25-hydroxyvitamin D (25-OHD) levels below 10 ng/ml (equivalent to <25 nmol/L) and "sufficient" Vitamin D as above 30 ng/ml (>50 nmol/L). Results The mean 25-OHD serum level was 12.4 (SD 7.3) ng/ml, (range 4.0-51.7 ng/ml). Forty nine percent (n = 158) were vitamin D deficient, with only 14 % (n = 45) meeting criteria for sufficiency. Accounting for age, gender, ethnicity and season of sampling, serum 25-OHD levels were negatively correlated with waist circumference (r = −0.220, p < 0.002), triglycerides (r = −0.160, p = 0.024), total cholesterol (r = −0.144, p = 0.043), fasting glucose (r = −0.191, p = 0.007), HbA1c (r = −0.183, p = 0.01), and serum CRP levels (r = −0.211, p = 0.003) and were linked to the presence of metabolic syndrome. Conclusions This is the largest cross sectional study of serum 25-OHD levels in community dwelling individuals with established psychosis, indicating a high level of vitamin D deficiency. Lower vitamin D levels are associated with increased cardiovascular disease risk factors and in particular metabolic syndrome. Further research is needed to define appropriate protocols for vitamin D testing and supplementation in practice to see if this can improve cardiovascular disease risk. Trial registration ISRCTN number isISRCTN58667926 Date of registration: 23/04/2010